Soil health: definitions, history, key concepts and hurdles - Wander, Michelle M. (Burleigh Dodds Series in Agricultural Science, 2023)
This chapter reviews the history and trajectory of soil quality and soil health as global scientific objectives. Sections review definitions and drivers, key concepts, and hurdles that change this field of effort before considering evolving methodologies.